Аналіз стейкхолдерів процесу підвищення енергоефективності у житлово-комунальному господарстві України - Павленко, Н. М. (Ways to Improve Construction Efficiency, 2012)
In the article discusses the main stages of the analysis of stakeholders improve energy efficiency in housing and communal services of Ukraine. Held categorization of stakeholders, developed maps of the resources and willingness to influence / power stakeholders.